Defining Quality in Undergraduate Education - Alison W. Bowers; Shyam Ranganathan; Denise R. Simmons (Laureate Education Inc, 2018)
Objectives: This research brief explores the literature addressing quality in undergraduate education to identify what previous research has said about quality and to offer future directions for research on quality in undergraduate education. Method: We conducted a scoping review to provide a broad overview of existing research. Using targeted search terms in academic databases, we identified and reviewed relevant academic literature to develop emergent themes and implications for future research. Results: The exploratory review of the literature revealed a range of thoughtful discussions and empirical studies attempting to define quality in undergraduate education. Many publications highlighted the importance of including different stakeholder perspectives and presented some of the varying perceptions of quality among different stakeholders. Conclusions: While a number of researchers have explored and written about how to define quality in undergraduate education, there is not a general consensus regarding a definition of quality in undergraduate education. Past research offers a range of insights, models, and data to inform future research. Implication for Theory and/or Practice: We provide four recommendations for future research to contribute to a high quality undergraduate educational experience. We suggest more comprehensive systematic reviews of the literature as a next step.